Lithic techno-complexes in Italy from 50 to 39 thousand years BP: An overview of lithic technological changes across the Middle-Upper Palaeolithic boundary. (20th June 2020) - Marciani, Giulia; Ronchitelli, Annamaria; Arrighi, Simona; Badino, Federica; Bortolini, Eugenio; Boscato, Paolo; Boschin, Francesco; Crezzini, Jacopo; Delpiano, Davide; Falcucci, Armando; Figus, Carla; Lugli, Federico; et al.
Abstract: Defining the processes involved in the technical/cultural shifts from the Late Middle to the Early Upper Palaeolithic in Europe (~50-39 thousand years BP) is one of the most important tasks facing prehistoric studies. Apart from the technological diversity generally recognised as belonging to the latter part of the Middle Palaeolithic, some assemblages showing original technological traditions (i.e. Initial Upper Palaeolithic: Bohunician, Bachokirian; so called transitional industries: Châtelperronian, Szeletian, Lincombian-Ranisian-Jerzmanowician, Uluzzian; Early Upper Palaeolithic: Protoaurignacian, Early Aurignacian) first appear during this interval. Explaining such technological changes is a crucial step in order to understand if they were the result of the arrival of new populations, the result of parallel evolution, or of long-term processes of cultural and biological exchanges. In this debate Italy plays a pivotal role, due to its geographical position between eastern and western Mediterranean Europe as well as to it being the location of several sites showing Late Mousterian, Uluzzian and Protoaurignacian evidence distributed across the Peninsula. Our study aims to provide a synthesis of the available lithic evidence from this key area through a review of the evidence collected from a number of reference sites. The main technical features of the Late Mousterian, the Uluzzian and the Protoaurignacian traditions are examined from a diachronic and spatial perspective. Our overview allows the identification of major differences in the technological behaviour of these populations, making it possible to propose a number of specific working hypotheses on the basis of which further studies can be carried out. This study presents a detailed comparative study of the whole corpus of the lithic production strategies documented during this interval, and crucial element thus emerge: 1. In the Late Mousterian tools were manufactured with great attention being paid to the production phases and with great investment in inizializing and managing core convexities; 2. In contrast, Uluzzian lithic production proceeded with less careful management of the first phases of debitage, mainly obtaining tool morphologies by retouching. 3. In the Protoaurignacian the production is carefully organized and aimed at obtaining laminar blanks (mainly bladelets) usually marginally retouched. These data are of primary importance in order to assess the nature of the "transition" phenomenon in Italy, thus contributing to the larger debate about the disappearance of Neandertals and the arrival of early Modern Humans in Europe.